Activation of microvesicle peripheral blood mononuclear cells by mesenchymal stem cells secretome co-cultivated with osteosarcoma stem cell - Fachrizal Arfani Prawiragara; Ferdiansyah; Mouli Edward; Dwikora Novembri Utomo; Mohammad Hardian Basuki; Alexander Patera Nugraha; Fedik Abdul Rantam (GarVal Editorial Ltda., 2022)
Context: Microvesicle is a cell micro molecule that may play a role in the process of osteosarcoma stem cell apoptosis. Aims: To investigate the activity of peripheral blood mononuclear cells (PBMCs) through the secretion of interleukin-2 (IL-2), interleukin-6 (IL-6), interleukin-10 (IL-10), C-X-C Motif Chemokine Ligand 13 (CXCL13) and tissue inhibitor of metalloproteinases-3 (TIMP-3) on co-cultivation of peripheral blood mononuclear cells (PBMCs) sensitized by mesenchymal stem cell secretome (MSCS) co-cultivated with osteosarcoma stem cells (OS-SCs). Methods: This study was true experimental with a post-test only control group design. This was in vitro study PBMSCs sensitized by MSCS as then samples were divided into 4 treatment groups, respectively: Zero-day treatment (P0) PBMCs were co-cultivated with OS-SCs for 0 hours; First treatment (P1) PBMCs were co-cultivated with OS-SCs for 1 hour; Second treatment (P2) PBMCs were co-cultivated with OS-SCs for 2 days; Third treatment (P3) PBMCs were co-cultivated with OS-SCs for 4 days. The examination method used in this study was flow cytometry and indirect enzyme-linked immunosorbent assay (ELISA). The data were statistically analyzed with analysis of variance (ANOVA) with a p≤0.05 considered a significant difference. Results: There was a tendency for a significant increase in extravesicular secretion in the secretion of IL-2, IL-6, IL-10, CXCL13, TIMP3, in the microvesicle PBMCs when sensitized by MSCs secretome co-cultivated with OS-SCs environment co-cultivated after the fourth day with significantly different between groups (p≤0.05). Conclusions: PBMSCs' microvesicle such as IL-2, IL-6, IL-10, CXCL13, TIMP3 was significantly sensitized by MSCS and co-cultivated with OS-SCs after the fourth day of in vitro.